Engaging in Interactive Book Reading: General Warming Up Before Exercising for Children - Sharita, Naima Syeeda (Bina Nusantara University, 2024)
Many parents are encouraging their children to exercise as a result of the COVID- 19 pandemic. Many others, on the other hand, do not warm up before participating in any sport. This is dangerous since it increases the risk of sprained muscles, cramping, and other problems. Warming up is crucial before exercising, yet many people are still unaware of the risks of not doing so. The objectives for this project is to create an interactive sports book. Unlike traditional books, this interactive book will use lift-the-flap, slide, or spin-the-wheel strategies to make learning more entertaining for children. To promote the socialization of young people through sports. As well as teaching children how to warm up with the assistance of adults. The method used is qualitative method. The results is It is clear from the in-depth interview and observation that many people still ignore the importance of warming up. Several children revealed in interviews that their teacher did not teach them how to warm up, and one of them learned about warming up via YouTube. Which means that the video that children see isn't always appropriate for their age group's warming up movement. According to the findings of the interviews, manipulating a scenario and performing fundamental movements is an effective technique to teach preschool children to warm up. The 7 Primal Movement Patterns is a great warm-up for children aged 3- 5 years. The seven basic movements are twist, push, pull, bend, squat, lunge, and gait. They represent the most basic breakdown of all human movements.